2016
DOI: 10.1038/srep26971
|View full text |Cite
|
Sign up to set email alerts
|

The NKD1/Rac1 feedback loop regulates the invasion and migration ability of hepatocarcinoma cells

Abstract: Hepatocellular carcinoma (HCC) is complicated by aggressive migration and invasion, which contribute to the increased mortality of HCC patients. The NKD1 protein is abnormally expressed in many neoplasms and plays an important role in tumor progression. However, the regulation and underlying molecular mechanisms of NKD1 in HCC cell invasion and migration remain poorly understood. In the present study, ectopic expression of NKD1 in HCC cells attenuated migration and invasion in vitro and in vivo by down-regulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
8
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 31 publications
3
8
1
Order By: Relevance
“…However, the underlying molecular mechanism of NKD1 in osteosarcoma cell invasion and migration remains unidentified. Recently, Li et al () showed that forced expression of NKD1 inhibited HCC cell migration and invasion in vivo and in vitro, which was inconsistent with our observations. They found that NKD1‐mediated regulation of HCC cell invasion and migration is dependent on Rac1.…”
Section: Discussioncontrasting
confidence: 99%
“…However, the underlying molecular mechanism of NKD1 in osteosarcoma cell invasion and migration remains unidentified. Recently, Li et al () showed that forced expression of NKD1 inhibited HCC cell migration and invasion in vivo and in vitro, which was inconsistent with our observations. They found that NKD1‐mediated regulation of HCC cell invasion and migration is dependent on Rac1.…”
Section: Discussioncontrasting
confidence: 99%
“…Ras‐related C3 botulinum toxin substrate 1 (RAC1) is a pleiotropic regulator of many cellular processes, including the cell cycle, cell‐cell adhesion, motility, and of epithelial differentiation . Recent studies showed that RAC1 worked as an oncogene in many tumors, including breast cancer, melanoma, and liver cancer . In the present study, we for the first time found that RAC1 was a direct target of miR‐365.…”
Section: Discussionsupporting
confidence: 63%
“…As such, prevention and treatment of HCC migration and invasion is of great importance for improving the prognosis of HCC patients [19]. EMT plays an important role in the process of metastasis; HCC cells can obtain mesenchymal characteristics though EMT, which enhance their capacity for movement [20].…”
Section: Discussionmentioning
confidence: 99%